2022
DOI: 10.3390/ijerph19052688
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening in Asbestos-Exposed Populations

Abstract: Asbestos exposure is the most important cause of occupational lung cancer mortality. Two large randomized clinical trials in the U.S. and Europe conclusively demonstrate that annual low-dose chest CT (LDCT) scan screening reduces lung cancer mortality. Age and smoking are the chief risk factors tested in LDCT studies, but numerous risk prediction models that incorporate additional lung cancer risk factors have shown excellent performance. The studies of LDCT in asbestos-exposed populations shows favorable resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The widespread under-recognition of occupational causes of lung cancer is a significant barrier to lung cancer prevention. In the past few years, numerous lung cancer screening programs have been established in several industrialized countries [ 44 ]. Two large randomized controlled trials show that periodic low-dose chest CT scanning reduces lung cancer mortality [ 45 , 46 ], but to date, age and smoking are the main risk factors for lung cancer to be eligible for those programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread under-recognition of occupational causes of lung cancer is a significant barrier to lung cancer prevention. In the past few years, numerous lung cancer screening programs have been established in several industrialized countries [ 44 ]. Two large randomized controlled trials show that periodic low-dose chest CT scanning reduces lung cancer mortality [ 45 , 46 ], but to date, age and smoking are the main risk factors for lung cancer to be eligible for those programs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the use of regular low-dose CT scans in the asbestos-exposed population has shown promising findings, but studies have mostly been modest in size, variable in design, and short-term in follow-up. It seems currently relevant to offer a regular low-dose CT screening for lung cancers to workers aged ≥50 years who have a history of five or more years of asbestos exposure, and it is now required to consider how to identify such workers and to organize screening programs with the help of public policy makers who have a key role in encouraging screening on a national level [ 44 ]. Our systematic screening process will help to reduce the under-reporting of occupational exposures in lung cancer and thus emphasize the need for screening programs in asbestos-exposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…That finding is in agreement with the results of other studies [ 16 , 43 ]. To target a population at greater risk, Markovitz et al [ 44 ] recommended LC screening for subjects exposed to asbestos for at least 5 years, and smoking with >10 pack-years with no limitation to the length of time as a former smoker, asbestosis, family history of LC, chronic pulmonary disease, prior cancer or an occupational co-exposure. Welsh et al [ 45 ] proposed LC screening for smokers exposed to asbestos, regardless of the number of pack-years of tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of asbestos exposure globally in the industrialized age and its known carcinogenic properties, it is not surprising that the screening and surveillance of asbestos‐exposed populations are relatively well studied 1–9 . The value of screening of asbestos‐exposed people by low‐dose computer tomography (LDCT) of the chest has not been confirmed in randomized clinical trials, but observational studies strongly suggest that LDCT is an effective tool for early lung cancer detection 10 . Most observational studies reviewed concluded that the criteria used to select individuals for LDCT may need broadening.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The value of screening of asbestos-exposed people by lowdose computer tomography (LDCT) of the chest has not been confirmed in randomized clinical trials, but observational studies strongly suggest that LDCT is an effective tool for early lung cancer detection. 10 Most observational studies reviewed concluded that the criteria used to select individuals for LDCT may need broadening.…”
mentioning
confidence: 99%